Management of Relapsed and Refractory Multiple Myeloma: Recent advances - Rathnam, Krishnakumar; Saju, S. V.; Honey, Susan Raju (Indian Journal of Medical and Paediatric Oncology, 2022)
Multiple myeloma (MM) accounts for ∼10% of total hematologic malignancies worldwide. In India, the incidence of MM has increased two-fold with marked heterogeneity. Significant improvements in terms of clinical outcomes have been observed in the management of MM in recent years. However, most patients develop a disease relapse with the first or subsequent treatments. A combination of immunomodulatory drugs (thalidomide and lenalidomide) and proteasome inhibitors (PIs; bortezomib) has been the mainstay for the therapeutic management of relapsed/refractory multiple myeloma (RRMM). This review highlights the management of RRMM with newer agents such as belantamab, carfilzomib, daratumumab, elotuzumab, ixazomib, mafadotin, selinexor, panobinostat, and venetoclax, with more focus on PIs. As a single agent and in combination with other drugs including dexamethasone and carfilzomib has been studied extensively and approved by the United States, European Union, and India. Clinical trials of these newer agents, either alone or in combination, for the treatment of RRMM in Western countries indicate survival, improved outcomes, and overall well-being. However, evidence in Indian patients is evolving from ongoing studies on carfilzomib and daratumumab, which will ascertain their efficacy and safety. Currently, several guidelines recommend carfilzomib-based, daratumumab-based, and panobinostat-based regimens in RRMM patients. Currently, with more accessible generic versions of these drugs, more Indian patients may attain survival benefits and improved quality of life.
Keywords: relapsed/refractory multiple myeloma; carfilzomib; Ixazomib; daratumumab; elotuzumab; panobinostat